Timed restricted feeding cycles drive daily rhythms in female rats maintained in constant light but only partially restore the estrous cycle - Guerrero-Vargas, Natalí N.; Espitia-Bautista, Estefania; Escalona, Rene; Lugo-Martínez, Haydée; Gutiérrez-Pérez, Mariana; Navarro-Espíndola, Raful; Setién, María Fernanda; Boy-Waxman, Sebastián; Retana-Flores, Elizabeth Angélica; Ortega, Berenice; Buijs, Ruud M.; Escobar, Carolina (Frontiers in Nutrition, 2022)
Light at night is an emergent problem for the modern society. Rodents exposed to light at night develop a loss of circadian rhythms, which leads to increased adiposity, altered immune response and increased growth of tumors. In female rats constant light (LL) eliminates the estrous cycle leading to a state of persistent estrous. The suprachiasmatic nucleus (SCN) drives circadian rhythms, and it strongly interacts with the neuroendocrine network necessary for the reproductive function. Our previous studies showed that daily restricted feeding-fasting cycles (RF) exert powerful entraining influence on the circadian system, they can influence the SCN activity and can restore rhythmicity or accelerate re-entrainment in experimental conditions of circadian disruption, like experimental shift-work or jet-lag. The present study explored RF in female rats exposed to LL, with the hypothesis that this cyclic condition can restore daily rhythms and the estrous cycle. Two different feeding schedules were explored: 1. A 12h restricted feeding - fasting cycle (RF), for which food was placed daily for 12h in the feeder or 2. A 12h feeding-fasting cycle with food access distributed in 4 events along the 12h corresponding to the feeding phase. Here we present evidence that scheduled feeding can drive daily rhythms of activity and temperature in rats exposed to LL, however, the protocol of distributed feeding pulses was more efficient to restore the day-night activity and core temperature as well as the c-Fos day-night change in the SCN. Likewise, the distributed feeding partially restored the estrous cycle and the ovary morphology in females under LL condition. Data here provided indicate that the 12h feeding – 12h fasting window determines the rest-activity cycle and can benefit directly the circadian and reproductive function.